2010
DOI: 10.1159/000303054
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Vastus Lateralis Muscle During an Acute Exacerbation of COPD

Abstract: Background/aims: The molecular mechanisms leading to loss in muscle force during an acute exacerbation in COPD patients are unknown. A cross-sectional study was designed to compare the gene expression profile of the vastus lateralis muscle in patients with an acute COPD exacerbation and in stable COPD patients. Methods: Muscle biopsies were taken in 9 COPD patients with an exacerbation on day 4 of hospitalization and in 15 stable COPD patients. Micro-array was performed on an UniSet Human 20K Bioarray. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 40 publications
3
64
1
Order By: Relevance
“…Another novel finding in the investigation is that muscle-wasted severe COPD patients exhibited greater protein ubiquitination levels in their atrophying muscles. In view of the present findings and of those previously published in limb [5][6][7] and respiratory muscles [8,39] of severe COPD patients, it could be assumed that the ubiquitin-proteasome system seems to play a relevant role in the process of muscle atrophy in severe COPD patients.…”
Section: Redox Balance and Content Of Key Muscle Proteinssupporting
confidence: 75%
See 2 more Smart Citations
“…Another novel finding in the investigation is that muscle-wasted severe COPD patients exhibited greater protein ubiquitination levels in their atrophying muscles. In view of the present findings and of those previously published in limb [5][6][7] and respiratory muscles [8,39] of severe COPD patients, it could be assumed that the ubiquitin-proteasome system seems to play a relevant role in the process of muscle atrophy in severe COPD patients.…”
Section: Redox Balance and Content Of Key Muscle Proteinssupporting
confidence: 75%
“…More recently, limb muscle mRNA levels of atrogin-1, but not MURF-1, were also shown to be upregulated in stable nonwasted severe COPD patients [7]. Additionally, MURF-1 and atrogin-1 mRNA levels were shown to be upregulated in the vastus lateralis of hospitalised nonwasted patients during an acute exacerbation [5]. Differences in the number of patients, their body composition, study conditions and in the methodologies employed in each case (mRNA expression versus protein content herein) might account for the minor discrepancies between studies.…”
Section: Redox Balance and Content Of Key Muscle Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Acute exacerbations of chronic obstructive pulmonary disease (COPD) are accompanied by pulmonary and transient systemic inflammation and malnutrition, which have been implicated in the onset of stepwise weight loss, muscle wasting and increased mortality (1)(2)(3)(4)(5)(6). The underlying mechanisms are unknown and difficult to unravel in patients during the acute phase of an exacerbation.…”
mentioning
confidence: 99%
“…Several mechanisms may contribute to this effect, such as nutritional imbalance [4], medications [5], physical inactivity [2], systemic inflammation [3] and oxidative stress [6,7]. It has been suggested that oxidative stress is increased in COPD patients during an acute exacerbation because these patients show increased plasma [6] and skeletal muscle [7] antioxidant capacities. Indeed, oxidative stress is already considered to play a major role in peripheral muscle dysfunction of COPD patients, both at rest and after exercise [8][9][10].…”
mentioning
confidence: 99%